l_p-Solutions of One Difference Equation in a Banach Space - Gorodnii, M. F. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We establish a criterion for the existence and uniqueness of solutions of a linear difference equation with an unbounded operator coefficient belonging to the space l_p(B) of sequences of elements of a Banach space B.